Enhanced stable long-term operation of biotrickling filters treating VOCs by low-dose ozonation and its affecting mechanism on biofilm. (November 2016) - Zhou, Qingwei; Zhang, Lili; Chen, Jianmeng; Luo, Yong; Zou, Haikui; Sun, Baochang
Abstract: For long-term operation of highly loaded biotrickling filters (BTFs), the prevention of excess biomass accumulation was essential for avoiding BTF failure. In this study, we proposed low-dose ozonation as a biomass control strategy to maintain high removal efficiencies of volatile organic compounds (VOCs) over extended operation of BTFs. To obtain an optimized biomass control strategy, the relative performance of five parallel BTFs receiving different ozone doses was determined, and the affecting mechanism of ozonation on biofilm was elucidated. Experimental results showed that the decline in ozone-free BTF performance began from day 150, which was correlated with excess biomass accumulation, abundant excretion of extracellular polymeric substances (EPS) and a decline in metabolic activity of biofilm over extended operation. Ozone of 5–10 mg m −3 was effective in preventing excessive growth and uneven distribution of biomass, and eventually maintaining long-term stable operations. Ozone of over 20 mg m −3 possibly inhibited microorganism growth severely, thereby deteriorating the elimination performance instead. Comparison of the biofilm EPS indicated that the presence of ozone reduce EPS contents to different extents, which was possibly beneficial for mass transfer and metabolic activity. Comparative community analysis showed that ozonation resulted in different microbial communities in the BTFs. Dyella was found to be the most abundant bacterial genera in all BTFs regardless of ozonation, indicating strong resistance to ozonation. Chryseobacterium and Burkholderia members were markedly enriched in the ozone-added biofilm, implying good adaptation to ozone presence. These findings provided an improved understanding of low-dose ozonation in maintaining a stable long-term operation of BTF. Highlights: Ozone was effective in preventing excess accumulation of biomass. Low-dose ozone contributed to the stable operation of biotrickling filters (BTFs). Control of ozone dose was a key strategy for achieving enhancing performance of BTFs. Ozone reduced the contents of extracellular polymeric substances within biofilm. Microbial community adapting to ozonation contributed to stable operation of BTFs.